Utility of Pax2 and Bcl-2 Immunohistochemical Stains in Detecting Early Endometrioid Endometrial Carcinoma. (21st September 2018) - Ye, Qiqi; Yoon, Esther; Han, Liying; Zhong, Minghao
Abstract: Objectives: Endometrioid endometrial carcinoma (ECC) is the most common type of tumor arising from endometrium. In contrast to serous carcinoma, the diagnostically useful immunohistochemical (IHC) markers for ECC are not available. Our aim is to assess the usefulness of Pax2 and Bcl-2 to detect early ECC from nonneoplastic proliferative endometrium. Methods: We used both tissue microarray (TMA) and regular whole tissue slides. In whole tissue section examination, we compared Pax2 and Bcl-2 expressions in 10 ECCs with adjacent nonneoplastic proliferative endometrium. TMAs containing 61 ECC cases with some paired normal endometrium alone and 10 serous carcinoma cases were constructed. Whole tissue section and TMA slides were stained for Pax2 and Bcl-2. The extension and intensity of staining were analyzed. We also develop a triple IHC stain for better visualization: Pax8 in red highlights nucleus of both ECC and benign proliferative endometrium; Pax2 and Bcl-2 in brown label only benign proliferative endometrium nucleus and cytoplasm, respectively. Results: For 61 TMA ECC cases, 58 (95.2%) showed reduced or complete loss of expression for both Pax2 and Bcl-2, 2 (3.2%) had retained high expression of Pax2 but reduced or negative Bcl-2 staining, and 1 (1.6%) had highly expressed Bcl-2 but complete loss of Pax2. For 10 regular whole tissue sections, all cases showed reduced or complete loss of expression for both Pax2 and Bcl-2. Serous carcinoma and secretory phase endometrium also demonstrated reduced or loss of expression of Pax2 and Bcl-2. In addition, triple staining can visually better distinguish early ECC from benign proliferative endometrium. Conclusion: Overall, our findings demonstrated that conjunctional staining of Pax2 and Bcl-2 may be of value in differentiating well-differentiated early ECC from nonneoplastic proliferative endometrium.